Are Children “Normal”? - Black, Dan A.; Kolesnikova, Natalia; Sanders, Seth G.; Taylor, Lowell J. (The Review of Economics and Statistics, 2013)
We examine Becker's (1960) contention that children are "normal." For the cross section of non-Hispanic white married couples in the U.S., we show that when we restrict comparisons to similarly-educated women living in similarly-expensive locations, completed fertility is positively correlated with the husband's income. The empirical evidence is consistent with children being "normal." In an effort to show causal effects, we analyze the localized impact on fertility of the mid-1970s increase in world energy prices - an exogenous shock that substantially increased men's incomes in the Appalachian coal-mining region. Empirical evidence for that population indicates that fertility increases in men's income.